Comprehensive clinical and metabolomics profiling of COVID-19 Mexican patients across three epidemiological waves - García-López, David Alejandro; Monárrez-Espino, Joel; Borrego-Moreno, Juan Carlos; Zheng, Jiamin; Mandal, Rupasri; Torres-Calzada, Claudia; Oropeza-Valdez, Juan José; Tenório Nunes, Alanne; Sánchez Rodríguez, Sergio Hugo; López, Jesús Adrián; Calzada Rodríguez, Blanca Estela; Wishart, David S.; et al. (Frontiers in Molecular Biosciences, 2025)
IntroductionAs of mid-2024, COVID-19 has affected over 676 million people worldwide, leading to more than 6.8 million deaths. Numerous studies have documented metabolic changes occurring during both the acute phase of the disease and the recovery phase, which, in some cases, contribute to the development of long COVID syndrome.Aims and methodsIn this study, we aimed to evaluate clinical, laboratory, and comprehensive metabolomic data from hospitalized COVID-19 patients during the second, third and fourth waves (Alpha, Delta, and Omicron). A targeted, fully quantitative metabolomics assay (TMIC MEGA Assay) was used to measure 529 metabolites and lipids in plasma samples. The metabolomic profiles of these patients were compared according to different and relevant factors impacting COVID-19 outcome, such as age, sex, comorbidities, and vaccination status.ResultsAmong the 21 classes of compounds evaluated in this study, amino acids and lipids were the most dysregulated when comparing age, sex, comorbidities, vaccination status, and the different epidemiological waves. This is the most comprehensive analysis in Mexico providing absolute quantitative data for 529 metabolites and lipids measured in hospitalized COVID-19 patients, which could be used to monitor their metabolic status and clinical outcomes associated with COVID-19 infection or with long COVID syndrome.